Cross-Cultural Adaptation and Psychometric Testing of the International Sedentary Assessment Tool for the Spanish Population - Cuesta-Vargas, Antonio; Roldán-Jiménez, Cristina; Martín-Martín, Jaime; González-Sánchez, Manuel; Gutiérrez-Sánchez, Daniel (MDPI, 2020)
Sedentary behavior (SB) is currently considered a public health problem with a high cost of care. Evaluating SB is essential for prevention and early management of physical inactivity. The International Sedentary Assessment Tool (ISAT) is an instrument that has been developed to assess SB. The aim of this study was to carry out a cross-cultural adaptation and a psychometric analysis of the Spanish version of the ISAT. A cross-sectional study was conducted. A total of 432 participants were included in this study. A double forward method and a backward method were used to translate the ISAT. A psychometric analysis of internal consistency and concurrent criterion validity was performed according to the most up-to-date Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN). No language difficulties were found in the translation process. The Spanish version of ISAT was readable and acceptable. Internal consistency was satisfactory (α = 0.80). Criterion validity was demonstrated (rho=0.63). The Spanish version of the ISAT is a valid and reliable measure that can be used clinically to assess SB. Further studies assessing other psychometric properties are needed.
Keywords: Ejercicio físico; Outcome measures; Physical activity; Psychometric properties; Questionnaires; Sedentary behavior; Validity